Fixed-bed adsorption of carbon dioxide onto ammonia-modified activated carbon : experimental and modeling study / Mohammad Saleh Shafeeyan - Shafeeyan, Mohammad Saleh (2015)
A commercial granular activated carbon (GAC) adsorbent was modified through an oxidation–amination process in an effort to increase its surface basicity and consequently enhance its CO2 adsorption capacity. To optimize the amination conditions of activated carbon adsorbents the effects of amination temperature, amination time, and the type of starting materials (variables) on the CO2 adsorption/desorption capacities of the adsorbents (responses) were investigated using a central composite design. The use of a pre-oxidized sorbent as a starting material and amination at 425 ºC for 2.1 h were found to be the optimum conditions for obtaining an efficient carbon dioxide adsorbent. The activated carbon modified at optimum conditions (OXA-GAC) exhibited CO2 adsorption and desorption capacity values of 26.47 mg/g and 95.4%, respectively. The promising characteristics of the OXA-GAC in terms of adsorption capacity (exhibiting an increase of 44% in capacity compared with the capacity of the GAC at 1 atm and 105 ºC) and multicycle durability make it suitable for practical applications. The equilibrium adsorption isotherms of CO2 on the GAC and the OXA-GAC were measured using a static volumetric method. CO2 adsorption measurements were performed at three different temperatures (303, 318, and 333 K) and pressures up to 1 atm. The obtained equilibrium data were fitted to the Freundlich, Sips, and Toth isotherms using a semi-empirical approach to differentiate the contributions of physical and chemical adsorption to the total CO2 uptake. The Toth semi-empirical equilibrium model provided the best fit to the experimental data, over the entire analyzed ranges of temperature and pressure. The isosteric heats of CO2 adsorption onto the GAC and OXA-GAC adsorbents were determined using the Clausius–Clapeyron equation. The initial isosteric heats of adsorption of 68 kJ mol-1 and 23 kJ mol-1 corresponded to the chemisorption and physisorption of CO2 on the OXA-GAC adsorbent, respectively, and these values were in excellent agreement with the zero-coverage heats of adsorption obtained using the temperature-dependent parameters of the proposed model. The kinetics of CO2 adsorption on the GAC and OXA-GAC adsorbents over the temperature range of 30–60 °C were studied using the pseudo-first-order, pseudo-second-order, and Avrami kinetic models. The best fit with the experimental kinetic data for both of the studied adsorbents was obtained by applying the Avrami kinetic model. Fixed-bed breakthrough experiments for CO2 adsorption onto the GAC and OXA-GAC adsorbents were performed by changing the adsorption temperature over the range of 30 to 60 °C and the feed flow rate from 50 to 100 ml min-1. The largest values of the CO2 equilibrium dynamic capacity (0.67 mol kg-1) and breakthrough time (10.9 min) over the range of operating conditions investigated were obtained using OXA-GAC adsorbent at 30 °C under a 50 ml min-1 feed flow rate. To predict the breakthrough behavior of the fixed-bed adsorption of CO2, a simple model was developed, including the Toth and Avrami equations to describe the equilibrium and kinetics of adsorption, respectively. The set of coupled differential equations was solved using a numerical approach based on the finite element method implemented in COMSOL Multiphysics software. The validity of the model predictions was evaluated by a comparison with the experimental data. The findings showed that the model predictions successfully fit the experimental data over the studied range of feed gas flow rates and adsorption temperatures.